2007
DOI: 10.1002/ibd.20062
|View full text |Cite
|
Sign up to set email alerts
|

Controversies surrounding the comorbidity of depression and anxiety in inflammatory bowel disease patients

Abstract: Psychological disorders are highly prevalent in patients with inflammatory bowel disease (IBD). Anxiety and depression are known to independently affect quality of life and may additionally impair quality of life in IBD over and above the IBD itself. Some researchers have further proposed that anxiety and depression may influence the clinical course of IBD. However, despite the potential for anxiety and depression to play an important role in the clinical picture of IBD, there is little prospective well-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
328
5
17

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(370 citation statements)
references
References 41 publications
20
328
5
17
Order By: Relevance
“…Our study also showed that the TNF-α rs1799724 C>T polymorphism increased the susceptibility to CD, which was in agreement with the results of 2 previous studies (Yang et al, 2006). Dysregulation of TNF-α is associated with the susceptibility to CD (Mikocka-Walus et al, 2007). It is well-known that TNF-α promoter polymorphisms affect gene expression (Mishra and Arankalle, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Our study also showed that the TNF-α rs1799724 C>T polymorphism increased the susceptibility to CD, which was in agreement with the results of 2 previous studies (Yang et al, 2006). Dysregulation of TNF-α is associated with the susceptibility to CD (Mikocka-Walus et al, 2007). It is well-known that TNF-α promoter polymorphisms affect gene expression (Mishra and Arankalle, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…A recent systematic review found that anxiety was present in 19% of IBD patients vs. 9.6% of the background population and depression was found in 21.2 with IBD vs. 13.4% in non-IBD controls. Th ere was just as much depression in those patients with inactive disease as measured by the Hospital Anxiety and Depression Scale as those with active disease ( 103 ). Th e impact of depression was measured in patients receiving infl iximab therapy for their active CD.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…CD can change quality of life, especially during flares, and may cause major changes in the physical, emotional and social lives of patients. CD has been associated with symptoms of anxiety and depression (10)(11)(12) . There is evidence that the continuous psychological suffering can exacerbate disease activity and increase the risk of a flare (13)(14)(15) .…”
Section: Introductionmentioning
confidence: 99%